Developing a Formative Construction Supply Chain Resilience Index to Improve Cost and Schedule Stability in Post-Disaster Projects - Lalu Marzuandi; Lalu Ibrohim Burhan (Research and Social Study Institute, 2026)
Background: Construction material supply chain resilience has emerged as a critical determinant of infrastructure project success in disaster-prone regions; however, its quantitative measurement at the post-disaster project level remains limited, particularly at the district scale. Despite East Lombok being an earthquake-affected area with intensive reconstruction activities, no empirical model has systematically quantified supply chain resilience and tested its influence on project cost and schedule performance.Aims: This study aimed to identify priority factors of construction material supply chain resilience and to examine the effect of a resilience index on post-earthquake project performance.Methods: An explanatory quantitative approach was applied to 25 reconstruction projects in East Lombok, involving eight experts for AHP weighting and multiple regression analysis of CPI and SPI using SPSS/Stata.Result: The results indicated that supplier diversification was the dominant factor (weight = 0.32) with acceptable consistency (CR = 0.069), while the average resilience index reached 0.64. The resilience index explained 46% of cost performance variance and 52% of schedule performance variance, demonstrating significant positive relationships (p < 0.05).Conclusion: These findings confirm that supply chain resilience functions as a risk-buffering mechanism for cost and schedule stability in post-disaster projects. The study provides an empirical operationalization of Supply Chain Resilience into a measurable AHP-based index.